2007
DOI: 10.1002/elps.200600632
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube detectors for microchip CE: Comparative study of single‐wall and multiwall carbon nanotube, and graphite powder films on glassy carbon, gold, and platinum electrode surfaces

Abstract: The performance of microchip electrophoresis/electrochemistry system with carbon nanotube (CNT) film electrodes was studied. Electrocatalytic activities of different carbon materials (single-wall CNT (SWCNT), multiwall CNT (MWCNT), carbon powder) cast on different electrode substrates (glassy carbon (GC), gold, and platinum) were compared in a microfluidic setup and their performance as microchip electrochemical detectors was assessed. An MWCNT film on a GC electrode shows electrocatalytic effect toward oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…In an effort to use an electrode material both more resistant to biofouling and possessing a larger potential range compared to noble metal electrodes [15][16][17], we developed a new method for the fabrication of carbon paste electrodes (CPEs) that optimizes their stability in a flow-based microfluidic device [18]. The greater stability of these CPEs results from exploiting beneficial properties of both soft and rigid composites, which are used as the binder, during CPE fabrication.…”
Section: Electrochemical Detection Methods For Cellular Stress Biomarmentioning
confidence: 99%
“…In an effort to use an electrode material both more resistant to biofouling and possessing a larger potential range compared to noble metal electrodes [15][16][17], we developed a new method for the fabrication of carbon paste electrodes (CPEs) that optimizes their stability in a flow-based microfluidic device [18]. The greater stability of these CPEs results from exploiting beneficial properties of both soft and rigid composites, which are used as the binder, during CPE fabrication.…”
Section: Electrochemical Detection Methods For Cellular Stress Biomarmentioning
confidence: 99%
“…The underlying bulk electrode is modified with CNT film, usually by the deposition of a suspension of CNTs in solvent (e.g. DMF or aqueous solution of a polymer) and allowing the solvent to evaporate [16,34,35,39,[43][44][45][46][47]. The CNTs consequently create a random CNT films on the surface of the electrodes.…”
Section: Carbon Nanotube-film Electrodesmentioning
confidence: 99%
“…The effects of the performances of different kinds of CNT, such as MWCNT and single-walled carbon nanotube (SWCNT), were studied by several groups. Using wellestablished probes as catecholamines, Pumera et al [45] demonstrated that a significant shift of the half-wave potentials to lower values is provided to the MWCNT film (E 1/2 shift of 0.08 and 0.08 V for dopamine and catechol, respectively) and the SWCNT film (E 1/2 shift of 0.10 V for catechol) when compared with a bare gold electrode. Crevillén et al [16] used a wide range of complex molecules for evaluating the performance of detectors.…”
Section: Carbon Nanotube-film Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies have been proposed to disperse CNTs in order to make possible their application for the development of electrochemical sensors [5][6][7][8][9] and electrochemical detectors in CE [10][11][12]. Dispersion in surfactants [13,14], solvents [15] polymers [16][17][18][19][20][21][22][23], mineral oil [24][25][26][27], and ionic liquids [28] have been successfully performed.…”
Section: Introductionmentioning
confidence: 99%